Pengaruh Pengembangan SDM dan Kompensasi Terhadap Kinerja Pelaku Pengadaan Barang/Jasa - Dini Anggreini Santiasari; Sulistiowati Sulistiowati (eCo-Buss, 2025)
This study aims to demonstrate the influence of human resource development and compensation on the performance of procurement actors in goods/services. The research used random sampling techniques and data collection was carried out in stages. The procurement actors in the Government of the City of Pontianak consist of Budget User (PA)/Proxy Budget User (KPA) as Commitment Making Officials (PPK), Procurement Officials, Selection Working Group, Other Personnel in the Government of the City of Pontianak, and Civil Servants (ASN) in the City Procurement Unit of Pontianak, with a population and sample size of 171 (one hundred seventy-one) people. This study uses Smart Partial Least Square (PLS) application, which is an alternative variance-based analysis method to calculate multiple linear regression methods. Based on the research results, it is concluded that human resource development has a positive and significant effect on the performance of procurement actors in goods/services in the government of the City of Pontianak, Compensation has a positive and significant effect on the performance of procurement actors in the government of Pontianak City, and Human Resource Development and Compensation jointly influence the performance of procurement actors in the government of Pontianak City.